Deep retroperitoneal fibromatosis including ureter, right iliac vessels and vaginal stump - Praderi, Raúl; Coiro, Miguel; Praderi, José; Vercelli, Jorge; Vignoli, Elena (Cirugía del Uruguay, 1994)
A multiparous patient who had undergone hysterectomy tour years earlier due to myomatosis, is seen because of a so/id tumor of right iliac fossa, not very painful, which caused hydronephrosis and obstruction of the right externa/ iliac vein. The tumor, which was so/id and well limited, was resected together with part of the right iliac veins and a fragment of urether. The ureteral stump was reimplanted in the bladder. The tumor disection took the vaginal stump to the place where it was implanted. lt was interpreted as a deep retroperitoneal fibromatosis originated in the vaginal stump and remains of the cervix. Evolution after three years was exce//ent.